Helicity dependent cross sections for the photoproduction of π0π± pairs from quasi-free nucleons - D. Ghosal; V. Sokhoyan; A. Fix; S. Lutterer; S. Abt; P. Achenbach; F. Afzal; Z. Ahmed; J.R.M. Annand; M. Bashkanov; R. Beck; M. Biroth; et al. (Physics Letters B, 2023)
Photoproduction of π0π±-pairs from quasifree nucleons bound in the deuteron has been investigated to study the helicity dependence of this reaction. Measurements with a liquid deuterium target were used to extract the unpolarized cross sections for reactions on protons and neutrons. A deuterated, longitudinally polarized solid-butanol target, together with a circularly polarized photon beam, determined the double polarization observable E. From these results the spin-dependent cross sections σ1/2 and σ3/2, corresponding to the anti-parallel and parallel spin configurations of the beam photon and target nucleon, have been derived. The measurements were performed at the Mainz MAMI accelerator with tagged, circularly-polarized photon beams produced via bremsstrahlung from longitudinally polarized electron beams. The reaction products were detected with an almost 4π solid-angle covering calorimeter composed of the Crystal Ball and TAPS detectors, supplemented by plastic scintillation detectors for charged particle identification. The results are sensitive to sequential decays of nucleon resonances via intermediate states and also to the decay of nucleon resonances by emission of charged ρ mesons, and are compared to recent model results.